2011
DOI: 10.1007/s00221-011-2980-9
|View full text |Cite
|
Sign up to set email alerts
|

Contact points during multidigit grasping of geometric objects

Abstract: We investigated the choice of contact points during multidigit grasping of different objects. In Experiment 1, cylinders were grasped and lifted. Participants were either instructed as to the number of fingers they should use, ranging from a two-finger grasp to a five-finger grasp, or could grasp with their preferred number of fingers. We found a strong relationship between the position of the fingertips on the object and the number of fingers used. In general, variability in the choice of contact points was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
0
25
2
Order By: Relevance
“…More generally, the core idea of optimal control is that behavior reflects the optimum of some cost function (Todorov and Jordan, 2002; Todorov, 2004). In the context of grasping, this general framework has been used to explain both how a set of contact positions (Friedman and Flash, 2007; Lukos et al, 2007, 2008; Ciocarlie et al, 2009; Fu et al, 2010, 2011; Craje et al, 2011; Gilster et al, 2012) and contact forces (Hershkovitz et al, 1997; Chalfoun et al, 2004; Pataky et al, 2004; Baud-Bovy et al, 2005; Niu et al, 2009; Terekhov et al, 2010) are selected. However, a problem with this framework is that it does not explain how the optimal solution might be actually computed in a biologically plausible manner.…”
Section: Force Synergiesmentioning
confidence: 99%
“…More generally, the core idea of optimal control is that behavior reflects the optimum of some cost function (Todorov and Jordan, 2002; Todorov, 2004). In the context of grasping, this general framework has been used to explain both how a set of contact positions (Friedman and Flash, 2007; Lukos et al, 2007, 2008; Ciocarlie et al, 2009; Fu et al, 2010, 2011; Craje et al, 2011; Gilster et al, 2012) and contact forces (Hershkovitz et al, 1997; Chalfoun et al, 2004; Pataky et al, 2004; Baud-Bovy et al, 2005; Niu et al, 2009; Terekhov et al, 2010) are selected. However, a problem with this framework is that it does not explain how the optimal solution might be actually computed in a biologically plausible manner.…”
Section: Force Synergiesmentioning
confidence: 99%
“…Several recent studies have shown that when such digit placement constraints are removed, subjects actively modulate contact points as a function of object properties such as mass distribution [14] or shape [15], [16], as well as planned manipulation [17], [18]. Most importantly, it has been shown that digit placement and forces are not independent and that their trial-to-trial covariation suggests the existence of high-level representations of learned manipulation task, i.e., the net torque that has to be generated for any combination of digit force and position [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the choice of fingertip contact points has been studied in most cases only for two-finger grasps that involved the thumb and index finger. This contrasts with the recent finding that the default grasp of humans seems to involve all five fingers [25]. In general, the small variability of contact points and the preshaping of the hand in early phases of the prehension movement indicate a preplanning in the choice of contact points [26].…”
Section: Related Workmentioning
confidence: 69%